Identification and exploration of opportunities: case studies in Paraná and Quebec (Gestão & Regionalidade, 2015)
The objective of the research was to understand the identification and the exploration of opportunities in two contexts. The research had a qualitative approach and the method used was case study. Four cases were studied, two in Quebec and two in state of Paraná. Few differences were identified related to the context, but the influence of context was identified in immigrants' condition, as well as the influence of networks, information and the role of the context, as pointed by previous studies. The results also revealed as the entrepreneurs built the opportunities, generating value for the environment and producing artifacts.